Brunette ambition ebook - Michele, Lea (2014)
The star of the hit show Glee shares her experiences and insider tips on beauty, fashion, inner strength, and more in an illustrated in an illustrated book that’s part memoir, part how-to, and part style guide.   Lea Michele is one of the hardest working performers in show business.  Whether she’s starring as Rachel Berry on Glee, rocking a glamorous look on the red carpet, recording her solo album, or acting as the spokesperson for L’Oreal, Lea is the ultimate multi-tasker.  She knows better than anyone that it is difficult to be your best self and keep things in perspective when your to-do list is overflowing and you are faced with challenges, so she’s developed a foolproof system for remaining healthy and centered.  In Brunette Ambition, she reveals the lessons and advice that have worked for her—from beauty and fashion secrets to fitness tips, and career insights.  Supplemented with never-before-seen photos and revealing anecdotes, it’s the book Lea wishes she’d had in her teens and early twenties: A practical and inspirational guide to harnessing tenacity and passion and living the fullest life, no matter what obstacles life puts in your way.